Analisis Erosi Dan Sedimentasi Waduk (Studi Kasus Waduk Way Jepara Kabupaten Lampung Timur) - Nengah Sudiane; Dyah Indriana Kusumaastuti; Afandi . (UNIVERSITAS LAMPUNG, 2012)
Dam and irrigation channels are utilized to supply irrigation in Way Jepara area. Way Jeparacannot optimally function because the catchment area is disturbed by illegal logging which mayincrease erosion rate as well as sedimentation to the dam. This research aims to analyze erosionwhich occurs in the catchment area and sedimentation in the dam. Erosion prediction model usedin this study is USLE (Universal Soil Loss Equation). From the analysis it is obtained that totalerosion (A) in the catchment area is 2307.01 ton/year or 156.41 ton/ha/year which is classified aserosion class III or medium. The highest erosion rate, 1552.63 ton/ha/year, occurs in Land UnitNo. 107 near Langkap Mountain which is classified as severe. From the analysis the problemsarose can be categorized into two groups, problem related to catchment area conservation andtechnical l problem directly related to the dam. Solution to the problems should be based onconservation as well as social welfare.